Structural changes of arboreal vegetation in a temperate forest of Durango, Mexico - Graciano Avila, Gabriel; Alanís Rodríguez, Eduardo; Aguirre Calderón, Oscar; González Tagle, Marco Aurelio; Treviño Garza, Eduardo; Mora Olivo, Arturo; Corral Rivas, Javier (Instituto de Ecología, A.C., 2020)
Background and Aims: Forest management causes changes in the composition, structure and functioning of the forest. The objective of this study was to compare the structure of tree species over a period of 10 years in a forest in Durango, Mexico. Methods: The data come from trees with DBH greater than or equal to 7.5 cm (at a height >1.3 m) located in permanent sites that were evaluated over a five-year interval (2007, 2012, 2017). Three height strata were defined for each year of measurement under the Pretzsch index methodology taking into account the highest height of each measurement. In each stratum, the structure was assessed through the importance value index (IVI), alpha diversity (α) with species richness (S) and the Shannon-Wiener index (H’). All dasometric variables per stratum of each measurement were compared with ANOVA of a factor to determine the existence of statistically significant differences between the evaluations. Key results: Although there was an increase in basal area, volume and coverage from 2007 to 2017, this was not statistically significant. Strata II and III showed the greatest increase in basal area and volume. The coverage was greater than 100%, with the highest contribution being stratum III. The composition of species was similar in the three measurements, with stratum III being the most diverse. Pinus durangensis was the species of greatest ecological importance in strata I and II, while Quercus sideroxyla presented greater relevance in stratum III. Conclusions: The comparison made over a period of 10 years (2007-2017) allowed us to determine that the tree vegetation of the evaluated community remains unchanged with respect to the diversity of species, while the basal area and volume tend to increase.